Open-label, multicentre safety study of vemurafenib in 3219 patients with BRAFV600 mutation-positive metastatic melanoma: 2-year follow-up data and long-term responders' analysis. (July 2017) - Blank, Christian U.; Larkin, James; Arance, Ana M.; Hauschild, Axel; Queirolo, Paola; Del Vecchio, Michele; Ascierto, Paolo A.; Krajsova, Ivana; Schachter, Jacob; Neyns, Bart; Garbe, Claus; Chiarion Sileni, Vanna; et al.
Abstract: Background: The orally available BRAF kinase inhibitor vemurafenib is an effective and tolerable treatment option for patients with metastatic melanoma harbouring BRAF V600 mutations. We assessed the safety of vemurafenib in a large population of patients with few alternative treatment options; we report updated 2-year safety. Methods: This was an open-label, multicentre study of vemurafenib (960 mg bid) in patients with previously treated or untreated BRAF mutation-positive metastatic melanoma (cobas ® 4800 BRAF V600 Mutation Test). The primary end-point was safety; efficacy end-points were secondary. An exploratory analysis was performed to assess safety outcomes in patients with long duration of response (DOR) (≥12 or ≥24 months). Results: After a median follow-up of 32.2 months (95% CI, 31.1–33.2 months), 3079/3219 patients (96%) had discontinued treatment. Adverse events (AEs) were largely consistent with previous reports; the most common all-grade treatment-related AEs were arthralgia (37%), alopecia (25%) and hyperkeratosis (23%); the most common grade 3/4 treatment-related AEs were squamous cell carcinoma of the skin (8%) and keratoacanthoma (8%). In the exploratory analysis, patients with DOR ≥12 months (n = 287) or ≥24 months (n = 133) were more likely to experience grade 3/4 AEs than the overall population. No new specific safety signals were observed with longer vemurafenib exposure. Conclusions: After 2 years' follow-up, safety was maintained in this large group of patients with BRAF V600 mutation-positive metastatic melanoma who are more representative of routine clinical practice than typical clinical trial populations. These data suggest that long-term vemurafenib treatment is effective and tolerable without the development of new safety signals. Highlights: We studied vemurafenib in BRAF V600 mutation-positive metastatic melanoma. After 2 years' follow-up, no new safety signals were seen and safety was maintained. Patients with long duration of response had good prognostic markers at baseline. Our results suggest that long-term vemurafenib is effective and tolerable.